Current Review of the literature: The importance of training during growth to prepare the adult skeleton for intensive tennis - Bass, S.; Ducher, G. (Medicine and Science in Tennis, 2006)
Playing and training for tennis exposes the dominant arm to repeated high mechanical strains. The ability of the body to adapt to these loads is evident by the clear differences in size of the playing and the non-playing arm. However, the ability of the skeleton to adapt optimally to these loads may be dependent on the timing of exposure to the load; this question is explored in the following review. The following four articles puts forward the case that training during growth may be an essential component required for maximising bone strength in the playing arm of adult tennis players. These articles explore how the age of starting may affect the osteogenic response; not only in bone mass but also in bone geometry and strength, and how skeletal benefits may be maintained when training is reduced or ceased. 1. Kannus P, Haapasalo H, Sankelo M, Sievänen H, Pasanen M, Heinonen A, Oja P, Vuori I. Effect of starting age of physical activity on bone mass in the dominant arm of tennis and squash players. Ann Intern Med. 1995;123(1): 27-31. 2. Haapasalo H, Sievänen H, Kannus P, Heinonen A, Oja P, Vuori I Dimensions and estimated mechanical characteristics of the humerus after long-term tennis loading. J Bone Miner Res. 1996; 11(6):864-72. 3. Bass SL, Saxon L, Daly RM, Turner CH, Robling AG, Seeman E and Stuckey S. The effect of mechanical loading on the size and shape of bone in pre-, peri-, and postpubertal girls: a study in tennis players. J Bone Miner Res. 2002;17(12):2274-80.